Surgical Findings in Transfusion-Associated Necrotizing Enterocolitis - Couselo, Miguel; Fonseca, Rosa; Mangas, Lucía; Vila, Juan José (European Journal of Pediatric Surgery, 2016)
Introduction The extent of intestinal damage in transfusion-associated necrotizing enterocolitis (TNEC) has been scarcely studied. The aim of this investigation was to study surgical findings in TNEC and determine their severity considering the extent of the disease and risk of bowel perforation.Materials and Methods Neonates who required surgical treatment for necrotizing enterocolitis (NEC) were studied retrospectively. Patients who developed NEC within 48 hours after a red blood cell transfusion (RBCT) formed group TR48 and patients who did not receive a RBCT 48 hours before the diagnosis of NEC became group CN (conventional NEC). Both groups were compared: main outcomes were the extent of the disease (isolated, multifocal, or panintestinal), the existence of perforated NEC, and mortality. Categorical variables were analyzed with the chi-square test and continuous variables with the Mann–Whitney u-test. The relationship between RBCTs 48 hours before the diagnosis and the extent of intestinal disease was evaluated by ordinal logistic regression.Results Forty-seven patients were included in the study: 16 patients in TR48 and 31 in CN. The odds ratio of multifocal or panintestinal NEC for patients in TR48 was 0.5 (95% CI: 0.148–1.68). Neonates in TR48 had a relative risk (RR) of perforated NEC of 1.2 (95% CI: 0.76–1.85). The RR of death was 1.55 (95% CI: 0.76–3.14) in group TR48.Conclusion No differences in surgical findings between TR48 and CN could be demonstrated in this investigation; therefore, the hypothesis that intestinal damage might be more severe in TNEC was not confirmed.
Keywords: necrotizing enterocolitis; blood transfusion; surgery; patient acuity